Occurrence and Hydrochemical Characteristics of Saline and Salty Springs in the Sichuan Basin of China. (9th May 2019) - Guo, Juan; Zhou, Xun; Zhang, Yuqi; Ta, Mingming; Wang, Yuan
Abstract : Water samples from saline and salty springs (geothermal wells, n = 64 ) with TDS of 2-83 g/L and temperature of 19-95°C were collected in the Sichuan Basin to explore the factors controlling the occurrence of the springs and the differences in hydrochemistry. The saline and salty springs mostly emerge at the margin of the basin where fault zones or anticlines occur, which are clearly controlled by the regional tectonic trend. The springs are mainly of SO4 -Na type in the western basin, SO4 -Ca·Na and HCO3 -Na type in the southwestern basin, Cl-Na and Cl·SO4 -Na type in the northeastern basin, and SO4 -Ca type in the eastern basin. Good correlation between Na and Cl, Ca and SO4, and Mg and SO4 suggests that the major ions of springs in the Sichuan Basin are from incongruent dissolution of halite, gypsum, dolomite, and magnesium sulfate minerals present in the outcropping Cretaceous and Triassic and Permian strata (sandstone, gypsum, or anhydrite layers or lens) in the western basin. The presence of marine carbonate (limestone and dolomite) interbedded with evaporites (gypsum and halite) in the eastern basin explains the good correlations between SO4 and Ca and between Na and Cl. The groundwater is continuously heated by geothermal heat flow. A conceptual model for the formation of the saline and salty springs is proposed that hypothesizes meteoric water infiltrates in the core of anticlines that occur in the carbonate rocks with fractures or in the fault zones. The water flows into the limbs of the anticlines or deep aquifers along fault planes. During its subsurface transport, incongruent dissolution of carbonates and evaporites (including anhydrite and halite) in the Lower and Middle Triassic strata occurs and the groundwater is heated. The discharge areas are often in the low-lying areas along the limbs of anticlines where carbonate rocks crop out, in the low-lying areas of local river valleys that cut noncarbonate rocks, or in the Yangtze Valley and its tributaries where groundwater flows upward through the Upper Triassic clastic rocks.